Asuhan Keperawatan pada Keluarga Ny. R dengan Gangguan Sistem Muskuloskeletal: Gout Arthritis di Desa Kalibuntu RT 04 RW 01 Kecamatan Losari Kabupaten Brebes - Lena Alfiana; Ahmad Zakiudin; Anna Maulina Lestari (Jurnal Mahasiswa Ilmu Kesehatan, 2024)
Gout arthritis, commonly known as gout, is a degenerative disease caused by abnormal purine metabolism, characterized by elevated levels of uric acid in the blood. (hiperurisemia). According to data from the World Health Organization, the number of people suffering from gout reaches 230 million, or 34.2% of all non-communicable diseases. In Indonesia, it is increasing. Gout disease based on age characteristics is particularly high in individuals aged ≥ 75 years (54.8%). Central Java is estimated to be around 2.6 - 47.2%, varying across different populations. The percentage of the population suffering from gout arthritis at Puskesmas Kecipir is 13.67%. The number of people affected is 3,084 out of 22,560 in the productive age group. In the village of Kalibuntu, the percentage of the elderly population suffering from gout arthritis is 9 out of 37. The purpose of this scientific paper is to provide nursing care for Mrs. R's family with musculoskeletal system disorders: gout arthritis in Kalibuntu Village, Rt 04 Rw 01, Losari District, Brebes Regency. The assessment results of Mrs. R's family indicate that they are unaware of gout arthritis, its causes, classification, symptoms, as well as how to prevent and manage gout arthritis when pain occurs. The nursing problems that arise are knowledge deficit and chronic pain.